Screening for bovine leukocyte adhesion deficiency, deficiency of uridine monophosphate synthase, bovine citrullinaemia and factor XI deficiency in Holstein cattle - KAYA, MUHAMMET; MEYDAN, HASAN; KIYMA, ZEKERIYA; ALAN, MUHAMMET; YILDIZ, MEHMET A (The Indian Journal of Animal Sciences, 2016)
Holstein cattle reared in Eskisehir region were monitored with respect to the genetic disorders defined as bovine leukocyte adhesion deficiency (BLAD), deficiency of uridine monophosphate synthase (DUMPS), bovine citrullinaemia (BC) and factor XI deficiency (FXID). To determine the presence of BLAD, DUMPS, BC and FXID genotypes, Holstein cattle (219) were sampled. Three BLAD and 2 FXID carriers were identified among the 219 Holstein cattle examined, while none of the cows carried DUMPS and BC. Current study demonstrated that carriers of BLAD and FXID are present in the Turkish Holstein population in Eskisehir region, although at a low frequency. Since, artificial insemination is widely used in these populations, determination of the carriers of hereditary disorders within the population of breeding sires has become essential. To prevent economic losses resulting from genetic disorders, it is advised to screen breeding sires for these genotypes. The aim of this study was to investigate existence and prevalence of BLAD, DUMPS, BC and FXID alleles in Holstein cattle reared in Eskisehir region by using PCR and PCR-RFLP methods.